New Class of Power Converter for Performing the Multiple Operations in a Single Converter: Universal Power Converter - Dhananjaya Mudadla; Devendra Potnuru; Raavi Satish; Almoataz Y. Abdelaziz; Adel El-Shahat (Energies, 2022)
Universal power converters (UPCs) have aroused significant attention in performing multiple operations in a single power converter. Furthermore, they contribute to economic operation and improved system performance. In this work, a new configuration of the universal power converter (UPC) was proposed by using a simple switching arrangement. It can perform different modes of operations, such as AC–DC, DC–DC, DC–AC, AC–AC, and cyclo-converter operations. In DC–DC conversion, the proposed configuration can perform buck mode, boost mode, and buck–boost mode of operations. Moreover, in DC–AC conversion, it gives better total harmonic distortion (THD). The effectiveness of the proposed configuration was verified by an extensive simulation, using MATLAB/Simulink environment. A low-power prototype circuit was designed to test the viability of the proposed circuit configuration and validated with simulation results.